Repurchase Intention of Gen Z on Shopee Marketplace: A Technology Acceptance Model Approach - Rahmawati, Ayu Febriyanti Dewi; Sudaryanto, Sudaryanto; Paramu, Hadi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
E-commerce has reshaped shopping behavior, especially among Generation Z, who prioritize convenience and speed. While Shopee continues to improve the user experience, it faces challenges in maintaining satisfaction and loyalty among this selective and promotion-sensitive group. This study investigates how perceived usefulness (PU), perceived ease of use (PEOU), and satisfaction influence repurchase intention within the Technology Acceptance Model (TAM) framework. A total of 182 Gen Z respondents from Lumajang, who had used Shopee in the past six months, were selected using purposive sampling. Data were analyzed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) approach. The data testing procedure included convergent validity, discriminant validity, and reliability testing to ensure the accuracy and consistency of measurement instruments. This was followed by structural model evaluation using R² and Q² values, as well as hypothesis testing through path coefficient analysis to assess the significance of the relationships among variables. The results revealed that most respondents were female (69.8%) and aged 20–21 years, with the majority having used Shopee more than five times. PU and PEOU significantly affect satisfaction and repurchase intention, while satisfaction mediates the relationship between PU, PEOU, and repurchase intention. These findings highlight the essential role of user experience in fostering repurchase behavior among Gen Z Shopee users.